2016
DOI: 10.1093/monist/onv036
|View full text |Cite
|
Sign up to set email alerts
|

Character, Caricature, and Gossip

Abstract: Gossip is rarely praised. There seems little virtuous that is about talking behind someone's back. Whether there is anything virtuous about gossip, however, depends on the kind of gossip. Some gossip is idle, but some evaluative gossip promulgates and enforces norms. When properly motivated, such gossip effects positive change in society and counts as gossiping well. The virtue of gossiping well even includes some kinds of false gossip, namely the sort that exaggerates a pre-existing trait, thereby creating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
0
17
0
6
Order By: Relevance
“…Second, the topic of gossip typically seems to involve some sort of norm violation, either by the subject or the speaker. Robinson (2016) distinguishes between evaluative and idle gossip. Evaluative gossip assesses the absent subject by some normative criterion; for example, BVanessa is lazy,B Ewan stole $20,^or, BSam has the ugliest haircut.^In these examples, the speaker negatively evaluates the subject for an alleged norm violation.…”
Section: A Triadic Relational Framework For Gossipmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the topic of gossip typically seems to involve some sort of norm violation, either by the subject or the speaker. Robinson (2016) distinguishes between evaluative and idle gossip. Evaluative gossip assesses the absent subject by some normative criterion; for example, BVanessa is lazy,B Ewan stole $20,^or, BSam has the ugliest haircut.^In these examples, the speaker negatively evaluates the subject for an alleged norm violation.…”
Section: A Triadic Relational Framework For Gossipmentioning
confidence: 99%
“…Behavior-based gossip only discusses one or a few of the subject's past behavior(s), and patiency gossip discusses not what the subject has done but what has been done to him. As Robinson (2016) emphasizes, forewarned is forearmed: trait-based gossip has significant potential to impact the subject. If the gossip is negative, it can lead to his ostracism as a means of protecting others from him.…”
Section: A Triadic Relational Framework For Gossipmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gossip is not simply a mode of information transference. In fact, Robinson (2016) suggested that gossip is generally encoded with some salacious or amusing item of information about a third party, although Cuonzo (2008) claims that any utterance can be considered gossip under certain conditions and not gossip under others.…”
Section: Gossipmentioning
confidence: 99%
“…Active gossipers may not be trusted to keep discrete information to themselves, and therefore will be less attractive as close friends (Ellwardt et al 2012). Robinson (2016) notes that gossip can arise as a desire for vengeance. Michelson and Mouly (2000) contend that it is largely motivated by the gossip's ego and competitiveness.…”
Section: Gossipmentioning
confidence: 99%